Should Queal outsource its production? - Hooft, Rogier van 't; Behne, Wiebke; Pitinov, Sergei; Dudas, Fanni; Hulsink, Willem (London : SAGE Publications Ltd, 2017)
Queal was founded in April 2014 by the two Dutch entrepreneurs Floris Wolswijk and Onno Smits, who were fascinated by the idea of powdered food and the business concept of the American pioneer, Soylent, in this emerging niche market. The product, a powder, is simply mixed with water and produces a shake containing all the daily nutrition and vitamins the human body needs. Soylent's founder published his recipe online and made it open use for everyone. Floris and Onno build on this recipe with an aim to improve it and introduce more variations in terms of kcal and flavors, based on customer preferences.The Queal founders started small and financed their start-up through bootstrapping. Production was performed by Floris and Onno themselves, who had acquired a clean, small room in their office building and turned it into a home laboratory. After successful trials with a few customers gathered from the internet, the entrepreneurs established their website with a web shop and constantly worked to improve their recipe and introduce more variations and flavours. Soon after, the company introduced shipping to 28 European countries and offered five product variations with seven tastes.
Originally Published In Van 't Hooft, R., Behne, W., Pitinov, S., Dudas, F., & Hulsink, W. (2016). Should Queal outsource its production? Rotterdam, Netherlands: Rotterdam School of Management, Erasmus University.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Queal -- Case studies; Small business -- Management -- Case studies; Small business -- Finance -- Case studies